The Portrayal of Worker Alienation in the Movie American Fiction (2023) (PANOPTICON: Journal of English Studies, 2025)
This study aims to identify the practices of alienation and examine how the main character, Monk, confronts and responds to his alienated condition. Directed by Cord Jefferson, American Fiction (2023) portrays the conflict between Monk—a Black writer—and the publishing industry that demands conformity to market-driven stereotypes. As financial pressures mount, Monk is forced to compromise his creative autonomy to meet both economic needs and external expectations. This study employs Karl Marx’s (1977) theory of alienation, which conceptualizes the estrangement of workers from their labor, the act of production, their species-being, and their fellow humans, due to exploitative capitalist conditions. Utilizing a qualitative approach, the research analyzes selected scenes and dialogues to identify how these dimensions of alienation manifest in Monk’s experiences. The findings reveal that Monk undergoes all four forms of alienation: from the product of his labor, from the process of writing, from his creative identity, and from others in his personal and professional life. Despite moments of resistance, Monk ultimately chooses to persist within the system of alienation in order to sustain his livelihood. This study highlights the psychological and existential dilemmas faced by creative workers under capitalism, offering insight into the commodification of art and identity in contemporary cultural production.